Museo lúdico para personas no videntes en Quito - Proaño Viteri, Karen Adriana (2016)
The proposal of the playful Museum for blind persons in Quito, in the Center of Contemporary Art, has as main objective the generation of an innovative space and multisensory through the intervention of architecture interior; where will raise different interactive exhibitions of the city of Quito. Allowing in this way to provide a contribution to the society, in particular to the population blind to promote their education and cultural growth. To be a patrimonial building was intervened fully in the interior, remain indispensable utilization of the architecture to give treatment to all spaces, improving this way the functionality, aesthetics and the interior distribution with the use of materials, textures, furniture, signaling and in particular the contribution of multisensory and technological mechanisms, to create dynamic spaces where people seers and blind will be able to experience the knowledge through the touch and smell. In this way it poses a functional architectural party, formal, technological and comforting. The project has an area of approximately 1500 m2, where you distribute the entrance hall, living room, administrative area, souvenir shop and a cellar; in turn, account with 5 exhibition halls. The concept used is Quito in Braille, which were obtained different ways to translate it into the design of the spaces, furniture, and textures for coatings. Has been obtained as a result, a proposal that complies with the objectives set and with the concept embodied in its interior architecture, without leaving aside the mechanisms, systems and technologies necessary to take a recreational space that provides security, comfort, ergonomics, functionality and mainly cultural education for seers and blind.